The Construction of Sundanese Culture in the News Discourse Published by Local Mass Media of West Java - Anshori, Dadang S (Bina Nusantara University, 2018)
This research identified the construction of Sundanese culture in the local mass media of West Java. Based on the phenomenon occurred, the culture could be interpreted in an accordance with the spirit of time and society. Within the national framework, this issue was not simple because the nationalism that was built on the plots of localism was not impossible to be changed. The research method employed the qualitative method. The data were the form of discourses contained in the local mass media. The results show that the language that is being used by the local media that describes the meaning of low bargaining of political position and national leadership. The construction of the local media in depicting the Sundanese culture is classified as the national, cultural, Islamic, and other aspects of culture. In the context of national leadership, the construction strengthens and affirms the faced condition and the reality. In terms of cultural relations with Islam, the local media shows the positive aspects of the condition and the history of the Sundanese people that has been known as a religious, ethnic group. In terms of the cultural relations with other aspects, the people of West Java are advised to make an inward reflection in viewing the existence of Sundanese culture within the national context. The ideologies that established by the local media towards the Sundanese culture are idealism, primordial, and pragmatism-realistic.